Polylactic acid-based copolymer and preparation method thereof

Synthesizing polylactic acid-based copolymers through simplified reaction steps solves the problems of poor brittleness, toughness and thermal stability of polylactic acid, and reduces production costs and achieves improvement of polylactic acid performance.

CN119823341AActive Publication Date: 2025-04-15CHENGDU ORGANIC CHEM CO LTD CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510111301.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Polylactic acid has limited its further application due to its strong brittleness, poor toughness and poor thermal stability. The existing methods for synthesizing high molecular weight polylactic acid have a long reaction time and harsh conditions, resulting in high production costs.

Method used

The first reaction is carried out by lactide and 1,4-butanediol to obtain a double-terminal hydroxyl polylactic acid prepolymer. The second reaction is followed by dimethyl carbonate and aliphatic diol to obtain a double-terminal hydroxyl aliphatic polycarbonate prepolymer, and finally undergoes chain extension reaction with diisocyanate to synthesize a polylactic acid copolymer.

Benefits of technology

This method simplifies the copolymerization reaction between polylactic acid and aliphatic polycarbonate, shortens the reaction cycle, reduces production costs, and improves the mechanical and thermal properties of polylactic acid-based copolymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823341A_ABST
    Figure CN119823341A_ABST
Patent Text Reader

Abstract

The invention discloses a polylactic acid-based copolymer and a preparation method thereof, and belongs to the technical field of high polymer materials. The invention solves the problems of how to carry out copolymerization reaction of polylactic acid and aliphatic polycarbonate through a simple and effective method to synthesize the polylactic acid-based copolymer so as to improve various properties of polylactic acid and reduce the product preparation cost in the prior art. The preparation method comprises the following steps: S1, carrying out first reaction on lactide and 1, 4-butanediol to obtain a dihydroxy-terminated polylactic acid prepolymer; s2, dimethyl carbonate and aliphatic dihydric alcohol are subjected to a second reaction, and a dihydroxy-terminated aliphatic polycarbonate prepolymer is obtained; and S3, carrying out a chain extension reaction on diisocyanate, the double-terminal hydroxyl polylactic acid and the double-terminal hydroxyl aliphatic polycarbonate to obtain the polylactic acid-based copolymer. The polylactic acid-based copolymer prepared by the method provided by the invention is simple and effective in synthesis process, relatively high in molecular weight and good in flexibility, can improve the performance of polylactic acid to different degrees, and is beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a polylactic acid-based copolymer and a preparation method thereof. Background Art

[0002] In recent years, with the continuous consumption of fossil energy, as well as the increasing pollution and cost of traditional polymer materials, people have been looking for new biodegradable polymer materials that are widely available and green and pollution-free. Among them, polylactic acid, as a member of the aliphatic polyester family, has received widespread attention because of its good biodegradability, biocompatibility and strong tensile strength. At the same time, polylactic acid is derived from biomass and is a renewable energy source. Therefore, polylactic acid has been used in the biomedical field for a long time, such as drug delivery, tissue engineering, stent materials, sutures, etc., and is currently receiving more and more attention in replacing traditional petroleum-based materials. However, polylactic acid has always been limited in its further application due to its strong brittleness, poor toughness and poor thermal stability. At the same time, the lactide ring-opening polymerization method currently used to synthesize high molecular weight polylactic acid has a long reaction time and harsh reaction conditions, which makes the production cost of polylactic acid high.

[0003] In view of the above-mentioned shortcomings of polylactic acid, the current research focus is to modify polylactic acid to further improve its mechanical properties and thermal properties and reduce production costs. Introducing flexible aliphatic polycarbonate segments into polylactic acid is an effective method to improve the mechanical properties of polylactic acid, among which copolymerization of aliphatic polycarbonate and polylactic acid is a common way of modification. At present, the common method of copolymerization modification is to synthesize copolymers of polylactic acid and aliphatic polycarbonate by ring-opening copolymerization of lactide and cyclic carbonate or CO2 / epoxide / lactide copolymerization, but these methods still have certain problems, such as harsh reaction conditions, long reaction cycle, relatively single product, and difficulty in further modification. Therefore, how to carry out copolymerization of polylactic acid and aliphatic polycarbonate by a simple and effective method to synthesize polylactic acid-based copolymers, thereby improving the various properties of polylactic acid and reducing the cost of product preparation, has very important economic value. Summary of the invention

[0004] In view of the problem in the prior art of how to carry out copolymerization of polylactic acid and aliphatic polycarbonate by a simple and effective method to synthesize a polylactic acid-based copolymer, thereby improving various properties of polylactic acid and reducing product preparation costs, the present invention provides a polylactic acid-based copolymer and a preparation method thereof.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A method for preparing a polylactic acid-based copolymer comprises the following steps:

[0007] S1: Lactide and 1,4-butanediol undergo a first reaction to obtain a double-terminated hydroxyl polylactic acid prepolymer, the structural formula of which is:

[0008]

[0009] Wherein, the value range of m and n is an integer of 5-30, which may be further preferably 10-25, and most preferably 15-20;

[0010] S2: Dimethyl carbonate and aliphatic diol undergo a second reaction to obtain a double-terminal hydroxyl aliphatic polycarbonate prepolymer, the structural formula of which is:

[0011]

[0012] Among them, the value range of K, L, P, and Q is an integer of 15-35, which may be further preferably 18-30, and most preferably 21-25;

[0013] S3: The diisocyanate, the dihydroxy-terminated polylactic acid and the dihydroxy-terminated aliphatic polycarbonate are subjected to a chain extension reaction to obtain a polylactic acid-based copolymer having the structural formula:

[0014]

[0015] Preferably, the molar ratio of lactide to 1,4-butanediol is (20-200):1, which may be further preferably (40-120):1, and most preferably (50-80):1; the molar ratio of dimethyl carbonate to aliphatic diol is (1-1.8):1, which may be further preferably (1-1.5):1, and more preferably 1.2:1; the ratio of the mass of the diisocyanate to the total mass of the dihydroxy-terminated polylactic acid and the dihydroxy-terminated aliphatic polycarbonate is 1:(5-30).

[0016] Preferably, the mass ratio of the dihydroxy-terminated polylactic acid to the dihydroxy-terminated aliphatic polycarbonate is (1-9): (9-1), more preferably (3-7): (7-3), and most preferably (4-6): (6-4).

[0017] Preferably, the temperature of the first reaction is 80-160°C, and the time is 0.5-6 hours, more preferably 100-140°C, and most preferably 120°C; the reaction time is preferably 0.5-6 hours, more preferably 1-5 hours, and most preferably 2 hours.

[0018] Preferably, the second reaction is divided into an ester exchange stage and a condensation polymerization stage: the reaction temperature in the ester exchange stage is 100-140°C, and can be further preferably 110-130°C, and most preferably 120°C; the time is 2-5 hours; can be further preferably 3-5 hours, and most preferably 4 hours; the reaction temperature in the condensation polymerization stage is 150-190°C, can be further preferably 160-180°C, and most preferably 170°C; the time is 2-5 hours, can be further preferably 3-5 hours, and most preferably 4 hours.

[0019] Preferably, the chain extension reaction is a melt polymerization reaction, the reaction temperature is 150-170°C, more preferably 160°C, the reaction time is 0.1-2 hours, more preferably 0.2-1 hour, most preferably 0.5 hour.

[0020] Preferably, the chain extender diisocyanate in S2 is one of hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), dicyclohexylmethane diisocyanate (HMDI), and lysine diisocyanate (LDI), and more preferably hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (HMDI), and most preferably hexamethylene diisocyanate (HDI).

[0021] Preferably, the chemical formula of the aliphatic diol in S2 is HO-(CH2) K -OH, wherein k=2 to 10. Further, the aliphatic diol is one or more of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.

[0022] Preferably, a catalyst is used in both the first reaction and the second reaction, and the mass ratio of lactide to the catalyst in the first reaction is (50-500):1, more preferably (100-400):1, and most preferably (150-300):1; the catalyst in the first reaction is one or more of stannous octoate, stannous chloride, sodium acetate, ferric chloride, sodium chloride, aluminum chloride, ferric chloride, and triethylamine;

[0023] In the second reaction, the ratio of the sum of the masses of dimethyl carbonate and aliphatic diol to the mass of the catalyst is (50-500):1, further preferably (200-400):1, and most preferably 300:1; the catalyst in the second reaction is one or more of stannous octoate, stannous chloride, sodium acetate, ferric chloride, sodium chloride, aluminum chloride, tetrabutyl titanate, and triethylamine.

[0024] Preferably, the ratio of the chain extender diisocyanate to the total mass of the dihydroxy-terminated polylactic acid and the dihydroxy-terminated aliphatic polycarbonate in S3 is 1:(5-50), more preferably 1:(10-30), and most preferably 1:20.

[0025] Preferably, the lactide is one or more of L-lactide, D-lactide and racemic lactide.

[0026] Preferably, the number average molecular weight of the double-hydroxy-terminated polylactic acid prepolymer is 1,000 to 12,000, more preferably 3,000 to 6,000, and most preferably 4,500.

[0027] Preferably, the first reaction, the second reaction and the chain extension reaction are carried out in a nitrogen atmosphere.

[0028] A polylactic acid-based copolymer is prepared by the preparation method of the polylactic acid-based copolymer, and its structural formula is:

[0029]

[0030] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0031] The invention provides a method for preparing a polylactic acid-based copolymer, comprising: synthesizing a polylactic acid prepolymer with double terminal hydroxyl groups and an aliphatic polycarbonate prepolymer with double terminal hydroxyl groups, and then using diisocyanate to melt chain extend to obtain a polylactic acid-based copolymer. Compared with the prior art, the invention directly synthesizes the hydroxy-terminated polylactic acid by ring-opening polymerization of lactide initiated by diol, has a simple synthesis process and a short reaction cycle, and can synthesize polylactic acid prepolymers with different molecular weights by controlling the reaction time; the invention synthesizes aliphatic polycarbonate prepolymers with different carbon chain lengths by melt ester exchange reaction of dimethyl carbonate and diols with different carbon chain lengths; the synthesized copolymer has good flexibility, and its mechanical properties and thermal properties are improved, and polylactic acid-based copolymers with different mechanical properties can be synthesized according to aliphatic polycarbonates with different carbon chain lengths; the invention has simple process technology, low reaction cost, and the copolymer has good biodegradability, and provides a new method for synthesizing multi-block polylactic acid-based copolymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a graph showing the nuclear magnetic resonance test results of the product of Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0034] Example 1

[0035] A method for preparing a polylactic acid-based copolymer comprises the following steps:

[0036] S1: Put 50g L-lactide, 0.63g 1,4-butanediol and 0.33g stannous octoate into a 100ml three-necked flask, and then add 50mL toluene as the reaction solvent for the first reaction to obtain a double-terminated hydroxyl polylactic acid prepolymer, then introduce nitrogen for 10 minutes to expel the air in the flask, and keep the reaction system closed. Immerse the three-necked flask in a 120°C constant temperature oil bath, turn on magnetic stirring, and react for 2 hours. After the reaction is completed, take out the reaction product and cool it, then fully dissolve it with dichloromethane and precipitate it with anhydrous ethanol, filter it, and dry it in a vacuum oven at 40°C for 24 hours to obtain a double-terminated hydroxyl polylactic acid prepolymer with a number average molecular weight of 4300;

[0037] S2: Put 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate into a 100ml three-necked flask, immerse the flask in an oil bath, heat the reaction mixture to 120°C at normal pressure, and react for 4h. Then heat the reaction system to 170°C until no fraction evaporates, gradually reduce the system pressure to 100Pa, and react for 4h. After the reaction, take out the reaction product, cool it, then fully dissolve it with dichloromethane and precipitate it with anhydrous ethanol, filter it, and dry it in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4800;

[0038] S3: Take 5g of the double-terminal hydroxyl polylactic acid prepolymer (PLLA-OH) prepared by S1 and 5g of the double-terminal hydroxyl aliphatic polycarbonate (PBC-OH) prepared by S2 and add them into a three-necked flask. First, pass N2 into the flask for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to make the molten prepolymer fully mixed, and then use a syringe to add 0.5g of chain extender HDI to the flask, so that the mechanical stirring rate is maintained at 300r / min, and stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product and dissolve it with dichloromethane, then precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polypentylene carbonate with a number average molecular weight of 39,000.

[0039] The high molecular weight polylactic acid-based copolymer in Example 1 was subjected to nuclear magnetic resonance testing, and the test results are as follows: Figure 1 The chemical shifts in the NMR spectrum correspond to the chemical shifts of the components in the copolymer, and the molecular weight increases, indicating that the three components do undergo chain extension reactions, and this method can successfully synthesize high molecular weight polylactic acid-based copolymers.

[0040] The tensile strength and elongation at break of the samples were measured at room temperature using an Instron universal testing machine (Model 4302, Instron Engineering Company, Canton, MA) with a crosshead speed of 50 mm / min. These samples were formed by coating with a film coating machine. The sample thickness was 0.15 mm and the width was 10 mm. The length of the sample between the two pneumatic grips of the testing machine was 20 mm. Six measurements were performed on each sample and the results were averaged. The test results are as follows: The elongation at break of the polylactic acid-based copolymer prepared in Example 1 of the present invention is 64.82%, which is greater than the elongation at break of pure polylactic acid by 2.88%.

[0041] The basic thermal properties of the sample were tested by differential scanning calorimetry (DSC), and the DSC test was performed by TADS2500. The sample was quickly heated to 160°C and held for 3 minutes to eliminate the thermal history, then cooled to -50°C at a rate of 10°C / min, and finally heated to 160°C again at the same rate. The test results are: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 1 of the present invention is 13.5°C, which is lower than the glass transition temperature of pure polylactic acid 48.2°C.

[0042] Example 2

[0043] This embodiment is basically the same as embodiment 1, except that: S2: 50g of dimethyl carbonate, 48.15g of 1,5-pentanediol and 0.33g of triethylamine are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 120°C at normal pressure and reacted for 4h. Then the reaction system is heated to 180°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is carried out for 3h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4700. The obtained polylactic acid-based copolymer has a number average molecular weight of 37,000.

[0044] The mechanical properties of the product prepared in Example 2 were tested in the same manner as in Example 1. The test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 2 of the present invention was 75.08%, which was greater than the elongation at break of pure polylactic acid by 2.88%.

[0045] The thermal properties of the product prepared in Example 2 were tested using the same method as in Example 1. The test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Example 2 of the present invention was 10.8°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0046] Example 3

[0047] This embodiment is basically the same as embodiment 1, except that: S2: 50g of dimethyl carbonate, 54.63g of 1,6-hexanediol and 0.35g of sodium chloride are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 130°C at normal pressure and reacted for 3h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is carried out for 4h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4600. The obtained polylactic acid-based copolymer has a number average molecular weight of 43,000.

[0048] The mechanical properties of the product prepared in Example 3 were tested in the same manner as in Example 1. The test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 3 of the present invention was 80.32%, which was 2.88% greater than the elongation at break of pure polylactic acid.

[0049] The thermal properties of the product prepared in Example 3 were tested using the same method as in Example 1. The test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Example 3 of the present invention was 8.1°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0050] Example 4

[0051] This embodiment is basically the same as embodiment 1, except that: S2: 50g of dimethyl carbonate, 61.11g of 1,7-heptanediol and 0.37g of ferric chloride are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 130°C at normal pressure and reacted for 4h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is continued for 5h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4600. The obtained polylactic acid-based copolymer has a number average molecular weight of 41,000.

[0052] The mechanical properties of the product prepared in Example 4 were tested by the same method as in Example 1. The test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 4 of the present invention was 98.10%, which was 2.88% greater than the elongation at break of pure polylactic acid.

[0053] The thermal properties of the product prepared in Example 4 were tested using the same method as in Example 1. The test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Example 4 of the present invention was 6.6°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0054] Example 5

[0055] This embodiment is basically the same as embodiment 1, except that: S2: 50g of dimethyl carbonate, 67.59g of 1,8-octanediol and 0.39g of tetrabutyl titanate are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 120°C at normal pressure and reacted for 4h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is continued for 4h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4500. The obtained polylactic acid-based copolymer has a number average molecular weight of 38,000.

[0056] The mechanical properties of the product prepared in Example 5 were tested by the same method as in Example 1. The test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 5 of the present invention was 124.67%, which was 2.88% greater than the elongation at break of pure polylactic acid.

[0057] The thermal properties of the product prepared in Example 5 were tested using the same method as in Example 1. The test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Example 5 of the present invention was 4.9°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0058] Example 6

[0059] This embodiment is basically the same as embodiment 1, except that: S2: 50g of dimethyl carbonate, 74.07g of 1,9-nonanediol and 0.41g of zinc chloride are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 120°C at normal pressure and reacted for 4h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is continued for 4h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4300. The obtained polylactic acid-based copolymer has a number average molecular weight of 42,000.

[0060] The mechanical properties of the product prepared in Example 6 were tested by the same method as in Example 1. The test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 6 of the present invention was 173.31%, which was 2.88% greater than the elongation at break of pure polylactic acid.

[0061] The thermal properties of the product prepared in Example 6 were tested using the same method as in Example 1. The test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Example 6 of the present invention was 3.3°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0062] Example 7

[0063] This embodiment is basically the same as Example 1, except that: S2: 50g of dimethyl carbonate, 80.56g of 1,10-decanediol and 0.44g of stannous octoate are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 120°C at normal pressure and reacted for 4h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is continued for 4h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4200. The obtained polylactic acid-based copolymer has a number average molecular weight of 39,000.

[0064] The mechanical properties of the product prepared in Example 7 were tested by the same method as in Example 1. The test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 7 of the present invention was 214.35%, which was greater than the elongation at break of pure polylactic acid by 2.88%.

[0065] The thermal properties of the product prepared in Example 7 were tested using the same method as in Example 1. The test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Example 7 of the present invention was 1.5°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0066] Example 8

[0067] This embodiment is basically the same as embodiment 1, except that: S2: 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 120°C at normal pressure and reacted for 4h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is continued for 4h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4800.

[0068] S3: Add 6g PLLA-OH and 4g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product, dissolve it with dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 41,000.

[0069] According to the method of the above technical solution, the mechanical properties of the product prepared in Example 8 were tested, and the test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 8 of the present invention was 58.87%, which was 2.88% greater than the elongation at break of pure polylactic acid.

[0070] According to the method of the above technical scheme, the thermal properties of the product prepared in Example 8 were tested, and the test results were as follows: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 8 of the present invention was 19.8°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0071] Example 9

[0072] This embodiment is basically the same as embodiment 1, except that: S2: 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate are put into a 100ml three-necked flask, the flask is immersed in an oil bath, and the reaction mixture is heated to 120°C under normal pressure and reacted for 4h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is continued for 4h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4800.

[0073] S3: Add 7g PLLA-OH and 3g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product, dissolve it with dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 36,000.

[0074] According to the method of the above technical solution, the mechanical properties of the product prepared in Example 9 were tested, and the test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 9 of the present invention was 55.35%, which was greater than the elongation at break of pure polylactic acid by 2.88%.

[0075] According to the method of the above technical solution, the thermal properties of the product prepared in Example 9 were tested, and the test results were as follows: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 9 of the present invention was 25.2°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0076] Example 10

[0077] This embodiment is basically the same as embodiment 1, except that: S2 puts 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate into a 100ml three-necked flask, immerses the flask in an oil bath, and heats the reaction mixture to 120°C at normal pressure for 3h. Then the reaction system is heated to 170°C until no fraction is evaporated, and the system pressure is gradually reduced to 100Pa, and the reaction is continued for 3h. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4500.

[0078] S3: Add 8g PLLA-OH and 2g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product, dissolve it with dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 34,000.

[0079] According to the method of the above technical solution, the mechanical properties of the product prepared in Example 10 were tested, and the test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Example 10 of the present invention was 48.12%, which was greater than the elongation at break of pure polylactic acid of 2.88%.

[0080] According to the method of the above technical scheme, the thermal properties of the product prepared in Example 10 were tested, and the test results were as follows: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 10 of the present invention was 30.8°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0081] Embodiment 11

[0082] This embodiment is basically the same as Example 1, except that: S1: 50g of lactide, 0.63g of 1,4-butanediol and 0.33g of stannous octoate are put into a 100ml three-necked flask, and toluene is added as a reaction solvent. Then, nitrogen is introduced for 10min to exhaust the air in the bottle, and the reaction system is kept airtight. The reaction vessel is immersed in a 120°C constant temperature oil bath, magnetic stirring is turned on, and the reaction is carried out for 1 hour. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a 40°C vacuum oven for 24h to obtain a double-terminated hydroxyl polylactic acid with a number average molecular weight of 2600.

[0083] S2: 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate were put into a 100ml three-necked flask, the flask was immersed in an oil bath, and the reaction mixture was heated to 120°C under normal pressure and reacted for 3h. Then the reaction system was heated to 170°C until no fraction was evaporated, and the system pressure was gradually reduced to 100Pa, and the reaction was continued for 3h. After the reaction was completed, the reaction product was taken out and cooled, and then fully dissolved in dichloromethane and precipitated with anhydrous ethanol. After filtration, it was dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4500, and polylactic acid-polybutylene carbonate with a number average molecular weight of 28,000 was obtained.

[0084] S3: Add 5g PLLA-OH and 5g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product, dissolve it in dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C to dry for 24h.

[0085] According to the method of the above technical solution, the mechanical properties of the product prepared in Example 11 were tested, and the test results were as follows: the elongation at break of the polylactic acid-based copolymer prepared in Example 11 of the present invention was 54.63%, which was greater than the elongation at break of pure polylactic acid by 2.88%.

[0086] According to the method of the above technical scheme, the thermal properties of the product prepared in Example 11 were tested, and the test results were as follows: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 11 of the present invention was 16.1°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0087] Example 12

[0088] This embodiment is basically the same as Example 1, except that: S1: 50g of lactide, 0.63g of 1,4-butanediol and 0.33g of stannous octoate are put into a 100ml three-necked flask, and toluene is added as a reaction solvent. Then, nitrogen is introduced for 10min to exhaust the air in the bottle, and the reaction system is kept airtight. The reaction vessel is immersed in a 120°C constant temperature oil bath, magnetic stirring is turned on, and the reaction is carried out for 3 hours. After the reaction is completed, the reaction product is taken out and cooled, and then fully dissolved by dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a 40°C vacuum oven for 24h to obtain a double-terminated hydroxyl polylactic acid with a number average molecular weight of 6400.

[0089] S2: 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate were placed in a 100ml three-necked flask, the flask was immersed in an oil bath, and the reaction mixture was heated to 120°C under normal pressure and reacted for 5h. Then the reaction system was heated to 170°C until no fraction was evaporated, and the system pressure was gradually reduced to 100Pa, and the reaction was continued for 5h. After the reaction was completed, the reaction product was taken out and cooled, and then fully dissolved in dichloromethane and precipitated with anhydrous ethanol. After suction filtration, it was dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 6200.

[0090] S3: Add 5g PLLA-OH and 5g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product, dissolve it with dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 37,000.

[0091] According to the method of the above technical solution, the mechanical properties of the product prepared in Example 12 were tested, and the test results were as follows: the elongation at break of the polylactic acid-based copolymer prepared in Example 12 of the present invention was 59.17%, which was greater than the elongation at break of pure polylactic acid by 2.88%.

[0092] According to the method of the above technical scheme, the thermal properties of the product prepared in Example 12 were tested, and the test results were as follows: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 12 of the present invention was 10.8°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0093] Embodiment 13

[0094] This embodiment is basically the same as embodiment 1, except that: S1: 50g of lactide, 0.63g of 1,4-butanediol and 0.33g of stannous octoate are placed in a 100ml three-necked flask, and toluene is added as a reaction solvent. Then, nitrogen is introduced for 10 minutes to expel the air in the bottle, and the reaction system is kept closed. The reaction vessel is immersed in a 120°C constant temperature oil bath, magnetic stirring is turned on, and the reaction is carried out for 4 hours. After the reaction is completed, the reaction product is taken out and cooled, then fully dissolved with dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 40°C for 24 hours to obtain double-terminated hydroxyl polylactic acid with a number average molecular weight of 8200;

[0095] S2: 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate were placed in a 100ml three-necked flask, the flask was immersed in an oil bath, and the reaction mixture was heated to 120°C under normal pressure and reacted for 6h. Then the reaction system was heated to 170°C until no fraction was evaporated, and the system pressure was gradually reduced to 100Pa, and the reaction was continued for 6h. After the reaction was completed, the reaction product was taken out and cooled, and then fully dissolved in dichloromethane and precipitated with anhydrous ethanol. After suction filtration, it was dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 8500.

[0096] S3: Add 5g PLLA-OH and 5g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product, dissolve it with dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 34,000.

[0097] According to the method of the above technical solution, the mechanical properties of the product prepared in Example 13 were tested, and the test results were as follows: the elongation at break of the polylactic acid-based copolymer prepared in Example 13 of the present invention was 42.30%, which was greater than the elongation at break of pure polylactic acid by 2.88%.

[0098] According to the method of the above technical scheme, the thermal properties of the product prepared in Example 13 were tested, and the test results were as follows: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 13 of the present invention was 7.4°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0099] Embodiment 14

[0100] This embodiment is basically the same as embodiment 1, except that: S3: Add 5g PLLA-OH and 5g PBC-OH into a three-necked flask, first pass N2 for 10min to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat to 160°C under N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10min to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 1 hour. After the reaction is completed, take out the copolymerization product, dissolve it with dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 26,000.

[0101] According to the method of the above technical solution, the mechanical properties of the product prepared in Example 14 were tested, and the test results were as follows: the elongation at break of the polylactic acid-based copolymer prepared in Example 14 of the present invention was 35.58%, which was greater than the elongation at break of pure polylactic acid of 2.88%.

[0102] According to the method of the above technical scheme, the thermal properties of the product prepared in Example 14 were tested, and the test results were as follows: the glass transition temperature of the polylactic acid-based copolymer prepared in Example 14 of the present invention was 15.4°C, which was lower than the glass transition temperature of pure polylactic acid, 48.2°C.

[0103] Comparative Example 1

[0104] This comparative example is basically the same as Example 1, except that: S1: 50g L-lactic acid, 2.5g 1,4-butanediol and 0.5g stannous octoate were put into a 100ml three-necked flask and subjected to polycondensation reaction under vacuum conditions. The pressure in the reaction bottle was 1000Pa, the temperature was 120°C, and the reaction lasted for 8 hours; then the pressure in the reaction bottle was reduced to 100Pa, the temperature was raised to 180°C, and the reaction was continued for another 8 hours to obtain a double-terminated hydroxyl polylactic acid prepolymer having a number average molecular weight of 3400.

[0105] S3: Add 5g PLLA-OH and 5g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 1 hour. After the reaction is completed, take out the copolymerization product, dissolve it in dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24 hours to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 18,000.

[0106] According to the method of the above technical solution, the mechanical properties of the product prepared in Comparative Example 1 were tested, and the test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Comparative Example 1 of the present invention was 28.25%.

[0107] According to the method of the above technical solution, the thermal properties of the product prepared in Comparative Example 1 were tested, and the test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Comparative Example 1 of the present invention was 26.3°C.

[0108] Comparative Example 2

[0109] This comparative example is basically the same as Example 1, except that: S1: 50g L-lactic acid, 2.5g 1,4-butanediol and 0.5g stannous octoate were put into a 100ml three-necked flask and subjected to polycondensation reaction under vacuum conditions. The pressure in the reaction bottle was 1000Pa, the temperature was 120°C, and the reaction lasted for 8 hours; then the pressure in the reaction bottle was reduced to 100Pa, the temperature was raised to 180°C, and the reaction was continued for another 8 hours to obtain a double-terminated hydroxyl polylactic acid prepolymer having a number average molecular weight of 3400.

[0110] S2: 50g of dimethyl carbonate, 48.15g of 1,5-pentanediol and 0.33g of triethylamine were put into a 100ml three-necked flask, the flask was immersed in an oil bath, and the reaction mixture was heated to 120°C under normal pressure and reacted for 4h. Then the reaction system was heated to 180°C until no fraction was evaporated, and the system pressure was gradually reduced to 100Pa, and the reaction was continued for 3h. After the reaction, the reaction product was taken out and cooled, and then fully dissolved in dichloromethane and precipitated with anhydrous ethanol. After filtration, it was dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4700. The number average molecular weight of the obtained polylactic acid-based copolymer was 27,000.

[0111] According to the method of the above technical solution, the mechanical properties of the product prepared in Comparative Example 2 were tested, and the test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Comparative Example 2 of the present invention was 64.08%.

[0112] According to the method of the above technical solution, the thermal properties of the product prepared in Comparative Example 2 were tested, and the test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Comparative Example 2 of the present invention was 12.1°C.

[0113] Comparative Example 3

[0114] This comparative example is basically the same as Example 1, except that: S1: 50g L-lactic acid, 2.5g 1,4-butanediol and 0.5g stannous octoate were put into a 100ml three-necked flask and subjected to polycondensation reaction under vacuum conditions. The pressure in the reaction bottle was 1000Pa, the temperature was 120°C, and the reaction lasted for 8 hours; then the pressure in the reaction bottle was reduced to 100Pa, the temperature was raised to 180°C, and the reaction was continued for another 8 hours to obtain a double-terminated hydroxyl polylactic acid prepolymer having a number average molecular weight of 3400.

[0115] S2: 50g of dimethyl carbonate, 54.63g of 1,6-hexanediol and 0.35g of sodium chloride were put into a 100ml three-necked flask, the flask was immersed in an oil bath, and the reaction mixture was heated to 130°C under normal pressure and reacted for 3h. Then the reaction system was heated to 170°C until no fraction was evaporated, and the system pressure was gradually reduced to 100Pa, and the reaction was continued for 4h. After the reaction, the reaction product was taken out and cooled, and then fully dissolved in dichloromethane and precipitated with anhydrous ethanol. After filtration, it was dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 4600. The number average molecular weight of the obtained polylactic acid-based copolymer was 35,000.

[0116] According to the method of the above technical solution, the mechanical properties of the product prepared in Comparative Example 3 were tested, and the test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Comparative Example 3 of the present invention was 71.55%.

[0117] According to the method of the above technical solution, the thermal properties of the product prepared in Comparative Example 3 were tested, and the test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Comparative Example 3 of the present invention was 10.5°C.

[0118] Comparative Example 4

[0119] This embodiment is basically the same as embodiment 1, except that: S1: 50g of lactide, 0.63g of 1,4-butanediol and 0.33g of stannous octoate are placed in a 100ml three-necked flask, and toluene is added as a reaction solvent. Then, nitrogen is introduced for 10 minutes to expel the air in the bottle, and the reaction system is kept closed. The reaction vessel is immersed in a 120°C constant temperature oil bath, magnetic stirring is turned on, and the reaction is carried out for 6 hours. After the reaction is completed, the reaction product is taken out and cooled, then fully dissolved with dichloromethane and precipitated with anhydrous ethanol, filtered and dried in a vacuum oven at 40°C for 24 hours to obtain double-terminated hydroxyl polylactic acid with a number average molecular weight of 10400;

[0120] S2: 50g of dimethyl carbonate, 41.67g of 1,4-butanediol and 0.31g of sodium acetate were placed in a 100ml three-necked flask, the flask was immersed in an oil bath, and the reaction mixture was heated to 120°C under normal pressure and reacted for 6h. Then the reaction system was heated to 170°C until no fraction was evaporated, and the system pressure was gradually reduced to 50Pa, and the reaction was continued for 8h. After the reaction was completed, the reaction product was taken out and cooled, and then fully dissolved in dichloromethane and precipitated with anhydrous ethanol. After suction filtration, it was dried in a vacuum oven at 30°C for 24h to obtain a double-terminal hydroxyl aliphatic polycarbonate with a number average molecular weight of 10200.

[0121] S3: Add 5g PLLA-OH and 5g PBC-OH into a three-necked flask, and first pass N2 for 10 minutes to exhaust the air in the flask. Then immerse the reaction vessel in an oil bath and heat it to 160°C in a N2 atmosphere. After the prepolymer is completely melted, turn on the mechanical stirring for 10 minutes to mix the molten prepolymer thoroughly, then add 0.5g of chain extender HDI into the flask with a syringe, keep the mechanical stirring rate at 300r / min, stir vigorously and react for 0.5h. After the reaction is completed, take out the copolymerization product, dissolve it with dichloromethane, precipitate it with anhydrous ethanol, and then put it into a vacuum oven at 30°C and dry it for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 19,000.

[0122] According to the method of the above technical solution, the mechanical properties of the product prepared in Comparative Example 4 were tested, and the test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Comparative Example 4 of the present invention was 13.5%.

[0123] According to the method of the above technical solution, the thermal properties of the product prepared in Comparative Example 4 were tested, and the test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Comparative Example 4 of the present invention was 35.5°C.

[0124] Comparative Example 5

[0125] This embodiment is basically the same as Example 1, except that 5g PLLA-OH and 5g PBC-OH are added to a three-necked flask, and N2 is first passed for 10min to exhaust the air in the bottle. Then the reaction vessel is immersed in an oil bath and heated to 160°C under a N2 atmosphere. After the prepolymer is completely melted, mechanical stirring is turned on for 10min to allow the molten prepolymer to be fully mixed, and then 0.5g of chain extender HDI is added to the flask with a syringe, so that the mechanical stirring rate is maintained at 300r / min, and the mixture is stirred vigorously and reacted for 3h. After the reaction is completed, the copolymer product is taken out and dissolved with dichloromethane, then precipitated with anhydrous ethanol, and then placed in a vacuum oven at 30°C and dried for 24h to obtain polylactic acid-polybutylene carbonate with a number average molecular weight of 18,000.

[0126] The mechanical properties of the product prepared in Comparative Example 5 were tested in the same manner as in Example 1. The test results showed that the elongation at break of the polylactic acid-based copolymer prepared in Comparative Example 5 of the present invention was 12.7%.

[0127] The thermal properties of the product prepared in Comparative Example 5 were tested in the same manner as in Example 1. The test results showed that the glass transition temperature of the polylactic acid-based copolymer prepared in Comparative Example 5 of the present invention was 38.9°C.

[0128] The test results of Examples 1-14 and Comparative Examples 1-5 are shown in Table 1:

[0129] Table 1

[0130]

[0131]

[0132] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. A method for preparing a polylactic acid-based copolymer, characterized in that: The following steps are involved: S1: lactide and 1,4-butanediol undergo a first reaction to obtain a double-terminated hydroxyl polylactic acid prepolymer; S2: dimethyl carbonate and aliphatic diol undergo a second reaction to obtain a dihydroxy-terminated aliphatic polycarbonate prepolymer; S3: subjecting the diisocyanate, the dihydroxy-terminated polylactic acid and the dihydroxy-terminated aliphatic polycarbonate to a chain extension reaction to obtain a polylactic acid-based copolymer.

2. The method for preparing a polylactic acid-based copolymer according to claim 1, characterized in that: The molar ratio of lactide to 1,4-butanediol is (20-200):1, the molar ratio of dimethyl carbonate to aliphatic diol is (1-1.8):1, and the ratio of the mass of the diisocyanate to the total mass of the dihydroxy-terminated polylactic acid and the dihydroxy-terminated aliphatic polycarbonate is 1:(5-30).

3. The method for preparing a polylactic acid-based copolymer according to claim 2, characterized in that: The mass ratio of the dihydroxy-terminated polylactic acid to the dihydroxy-terminated aliphatic polycarbonate is (1-9):(9-1).

4. The method for preparing a polylactic acid-based copolymer according to any one of claims 1 to 3, characterized in that: The temperature of the first reaction is 80-160° C., and the time is 0.5-6 hours.

5. The method for preparing a polylactic acid-based copolymer according to any one of claims 1 to 3, characterized in that: The second reaction is divided into an ester exchange stage and a condensation polymerization stage: the reaction temperature of the ester exchange stage is 100-140°C and the time is 2-5 hours; the reaction temperature of the condensation polymerization stage is 150-190°C and the time is 2-5 hours.

6. The method for preparing a polylactic acid-based copolymer according to any one of claims 1 to 3, characterized in that: The chain extension reaction is a melt polymerization reaction, the reaction temperature is 150-170° C., and the reaction time is 0.1-2 hours.

7. The method for preparing a polylactic acid-based copolymer according to any one of claims 1 to 3, characterized in that: The chemical formula of the aliphatic diol in S2 is HO-(CH2) K -OH, wherein k=2~10.

8. The method for preparing a polylactic acid-based copolymer according to any one of claims 1 to 3, characterized in that: Catalysts are used in both the first reaction and the second reaction, and the mass ratio of lactide to catalyst in the first reaction is (50-500):1, and the ratio of the sum of the mass of dimethyl carbonate and aliphatic diol to the mass of catalyst in the second reaction is (50-500):

1.

9. A polylactic acid-based copolymer, characterized in that: The polylactic acid-based copolymer is prepared by the preparation method of any one of claims 1 to 8, and its structural formula is:

Citation Information

Patent Citations

  • Polylactic-acid block copolymer and its preparing method

    CN101024696A

  • Poly(alkene carbonate) diol-poly(lactic acid) block copolymer and preparation method thereof

    CN101735433A

  • Method for preparing polylactic acid-based high-elasticity copolymer

    CN101899139A

  • Biodegradable material and preparation method and application thereof

    CN102399417A

  • Polylactic acid segmented copolymer and preparation method thereof

    CN115785458A